EVALUASI LAPORAN AKUNTABILITAS KINERJA INSTANSI PEMERINTAH PADA SATUAN KERJA NON VERTIKAL TERTENTU PENYEDIAAN PERUMAHAN PROVINSI SULAWESI UTARA - Wantah, Kezia Princesa; Kalangi, Lintje; Tangkuman, Steven (Universitas Sam Ratulangi, 2020)
LAKIP is the government’s accountability for activities carried out within one budget year and as one of the realization of good governance. The community questioned whether the budget used was appropriate or not with what they received.In addition, accountability reports on public sector organizations are only oriented to